Percutaneous Pedicle Screw Placement in the Lumbar Spine: A Comparison Study Between the Novel Guidance System and the Conventional Fluoroscopy Method. Issue 9 (November 2015) - Unknown
Abstract : Study Design: The clinical study was conducted on 145 patients who received either a novel guidance method or a conventional fluoroscopic method for the percutaneous pedicle screw placement in the lumbar spine. Objective: The aim of this study was to introduce a novel guidance method for percutaneous pedicle screw placement and to compare it with the conventional fluoroscopic method. Summary of Background Data: Conventional fluoroscopic method was associated with a long screw placement and a more fluoroscopy time. The novel guidance system effectively minimized the insertion and the radiation exposure times. Methods: A total of 145 patients were divided into 2 groups. A total of 65 patients (group A) underwent 152 percutaneous pedicle screw fixation by conventional fluoroscopic method. A total of 80 patients (group B) underwent 185 percutaneous pedicle screw fixation by a novel guidance method. Age, body mass index, and sex ratio were comparable between the 2 groups ( P >0.05). The time of insertion, radiation exposure, and accuracy of the screw placement between the 2 groups were compared. Results: The mean time for a single pedicle screw placement was found to be 15.11±3.32 minutes in group A and 10.35±2.82 minutes in group B, respectively. The average radiation exposure was 9.06±2.15 s in group B and 13.07±3.06 s in group A, respectively. The differences were statistically significant for both screw placement and radiation exposure times ( P <0.05). A total of 131 screws (86.2%) in group A and 163 screws (88.1%) in group B were perfectly located within the pedicle. The statistical difference was not significant (χ 2 =0.277, P =0.598). Conclusions: The novel guidance system significantly reduced the insertion time and radiation exposure, provided the screw placement was accurately performed when compared with the conventional method.